Automatic Annotation of Enhanced Universal Dependencies for Brazilian Portuguese - de Souza, Elvis A.; Duran, Magali S.; Nunes, Maria das Graças V.; Sampaio, Gustavo; Belasco, Giovanna; Pardo, Thiago A. S. (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2024: Anais do XV Simpósio Brasileiro de Tecnologia da Informação e da Linguagem HumanaDO - 10.5753/stil.2024.245342, 2024)
This paper presents the first attempt to automatically annotate Enhanced Universal Dependencies for Brazilian Portuguese. We use a symbolic annotation system, based on graph rewriting rules, and modify its original rules to better suit the linguistic characteristics of Portuguese using a manually annotated sample from the journalistic portion of Porttinari treebank as ground truth. Our objective is to assess the performance of the automatic annotation for a novel language and to determine the extent of possible improvements through rule modifications. Results demonstrate significant performance enhancements, where linguistic-driven rule adjustments improved the annotation accuracy 11.38 points, achieving 96.05% F1-score.